Enterprise Rent-a-Car - Busse, Meghan R. (Meghan Ruth); Swinkels, Jeroen M.; Merkley, Greg ([London] : SAGE, 2016)
The company that would become Enterprise Rent-A-Car was started in 1957. By 2010, Enterprise had more than 6,000 rental locations in the United States and a fleet of 850,000 cars in service: its parent, Enterprise Holdings (comprising Enterprise, National and Alamo brands) accounted for nearly half of the car rental market and was more than twice the size of Hertz, the number two competitor. This case examines Enterprise's competitive advantage in the car rental sector.
Originally Published in: Busse, M., Swinkels, J., & Merkley, G. (2011). Enterprise Rent-A-Car (case revised 21/03/2012; teaching note revised 29/06/2012). 5-311-508. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Enterprise Rent-A-Car.; Performance -- Management -- Case studies; Competition -- Case studies; Corporate culture -- Case studies